Analisis Penerapan Metode Bernyanyi dalam Pembelajaran Kosakata Bahasa Arab di Sekolah Dasar - Afifah Fithryatu Shalihah; Zahrodin Fanani (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe and analyze the implementation of the singing method in improving Arabic vocabulary mastery among second-grade students of class 2D at SDIT Hidayaturrahman 1 Sragen for the academic year 2025/2026. The subjects of this study were the Arabic language teacher and 26 students of class 2D at SDIT Hidayaturrahman 1. This study employed a descriptive qualitative approach. Data collection included interviews, observation, and documentation as primary sources, while student examination scores and literature review served as supporting data. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing. The findings of this study indicate that students, particularly those in the early grades, experienced significant difficulties in memorizing Arabic vocabulary without the application of a specific learning method. This was largely attributed to the students' limited ability to comprehend the vocabulary being taught. In response, the teacher sought alternative solutions by developing varied Arabic learning strategies, one of which was the singing method. This method proved to be highly suitable as it facilitated the memorization of Arabic vocabulary more effectively, particularly for students at SDIT Hidayaturrahman 1 Sragen. Although a small number of students still obtained unsatisfactory scores, the singing method was demonstrated to be effective in the learning process. This effectiveness was evidenced by the examination results, in which 77% of the students achieved satisfactory scores